DIFFERENCES IN STUDENTS' MATHEMATICS LEARNING RESULTS AND MOTIVATION USING THE MONTESSORI METHOD AND THE CONVENTIONAL METHOD - Ani Finurika; Sudarsri Lestari; Mufidah Yusroh; Erisy Syawiril Ammah (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to: (1) determine the differences in students' mathematics learning outcomes between using the Montessori method and using the conventional method;(2) determine the differences in students' mathematics learning motivationbetween using the Montessori method and the conventional method. This study is a quantitative experimental study, with a pretest-posttest control group design. The population in this study were students of class III MI Al-Ikhsan, with a total of 46students. Meanwhile, the determination of the sample in this study used a saturated sample, which means that the samples used in the study were all members of the population. The study was conducted in April-May 2024. The data collection processin this study used tests and questionnaires. The data analysis techniques used were normality tests, homogeneity tests, and independent sample t-tests using SPSS. The results of this study are: (1) based on the results of the Independent Sample t-testof learning outcomes, the Sig. (2-tailed) value is (0.001 <0.05), this means that there are differences in the mathematics learning outcomes of students of class III MI AlIkhsan who use the Montessori method and students who use the conventional method; (2) Based on the results of the independent sample t-test for learning motivation, the Sig.(2-tailed) value is (0.000<0.05), this means that there is a difference in the motivation to learn mathematics between class III students at MI Al-Ikhsan who use the Montessori method and students who use the conventional method.